Implementasi Sistem Pendukung Keputusan Penentuan Calon Legislatif Dengan Menggukan Metode Simple Additive Weighting (Studi Kasus: Partai Demokrat Sumatera Utara) - Yusmei Gulow (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2021)
Information system is a very important thing in making a decision. Because the information system has a very high value, so that decisions are taken more quickly and accurately, it must be supported by relevant and accurate data capable of being used by each party in supporting the progress of the organization or company in achieving goals in making good decisions, for this reason members the title "implementation of the decision holder system for determining legislative candidates using the Simple Additive Waighting (SAW) method". Many agencies use computers as a tool to further improve the quality for the agency. By using a computer, the data processing process is carried out quickly and accurately so as to produce data in the form of information, one of which is information on determining legislative candidates for North Sumatra, Medan. The purpose of this system is to make it easier to get information about legislative candidates quickly and accurately. Thus, from the results of the system, it will facilitate the work process of employees in the North Sumatra Medan Democratic Party because the information on determining the required legislative candidates will be processed more quickly.